Interference with ADAM17 inhibits proliferation of human cervical cancer cell line HeLa - ZHANG Chun-li, QI Jie-hua, HUAN Yu, WU Shou-le, CAI Xu-shan (Jichu yixue yu linchuang, 2022)
Objective To investigate the effect of ADAM17 on proliferation of cervical cancer cells in vitro and its mechanism. Methods The specific shRNA against ADAM17 was transfected into HeLa cells. Western blot and RT-qPCR were used to examine the interference efficiency. The relative rates of proliferation were determined by CCK-8 assay. The migration and invasion were evaluated by scratch test and Transwell test.Western blot was used to detect the protein expression of PCNA, EGFR, p-EGFR, ERK and p-ERK in each group. Results The expression of ADAM17 mRNA and protein were decreased in HeLa cells transfected by sh-ADAM17(P＜0.05).ADAM17 had no effect on migration and invasion of cervical cancer cells,but ADAM17 interference significantly inhibited the proliferation of cervical cancer HeLa cells(P＜0.05). The expression of PCNA, p-EGFR and p-ERK protein was down-regulated(P＜0.05). Conclusions Interfering with ADAM17 can inhibit the proliferation of human cervical cancer cell line HeLa, which may be related to EGFR/ERK signaling pathway.